Festival Segoro Topeng Kaliwungu sebagai Strategi Pelestarian Kesenian Tradisional di Kabupaten Lumajang - Lily Meilan Rahmawati; Setyo Yanuartuti; Syaiful Qadar Basri (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
The development of globalization and modern culture has caused the existence of traditional arts to face various challenges, especially the declining interest of the younger generation in local culture. Therefore, preservation efforts are needed that are able to maintain the continuity of traditional arts so that they remain known and develop in society. This research aims to examine strategies for preserving the Kaliwungu Mask art through the Kaliwungu Mask Segoro Festival from a cultural preservation perspective. The Kaliwungu Mask is a development of the Madurese Getak Mask which underwent an acculturation process in Kaliwungu Village, Tempeh District, Lumajang Regency. The method used in this research is descriptive qualitative with data collection techniques through interviews, observation and documentation. Gigih Enggarjati was the main informant and festival organizer in this research. The research results show that the preservation strategy is carried out through organizing festivals as the main media which functions as a means of promotion, cultural education and artist regeneration. Conservation efforts are also supported by educational institutions, studios and arts communities that actively teach the Kaliwungu Mask dance. However, there are several obstacles in its implementation, such as limited human resources, facilities and infrastructure, coastal environmental conditions, as well as the potential for a shift in philosophical values ​​due to the development of creativity. This research shows that the Kaliwungu Segoro Mask Festival has an important role as a medium for cultural preservation as well as strengthening the local cultural identity of the people of Lumajang Regency